Corruption, Political Instability and Growth: Evidence from the Arab Spring - Hany Mohamed (SSRN Electronic Journal, 2018)
This paper empirically investigates the relationship between corruption, political instability, and economic growth. We first show how these variables interact by allowing for bidirectional causality between each two of the three variables for which we employ a panel VAR model on a dataset of 140 countries over the period of 1990-2017. Then, we exploit the incidence of the Arab Spring, as an exogenous shock, to measure the short-term effects of political shocks on corruption levels, political stability and economic growth using the difference-in-differences (DiD) framework.